Traditional Structures in Turkey and Greece in 30 October 2020 Aegean Sea Earthquake: Field Observations and Empirical Fragility Assessment - Aktas, Yasemin D; Ioannou, Ioanna; Malcioglu, Fatma Sevil; Vatteri, Ahsana Parammal; Kontoe, Maria; Donmez, Kokcan; Black, Jacob; Kazantzidou-Firtinidou, Danai; Dermanis, Panagiotis; Diri‐Akyildiz, Filiz (Frontiers in Built Environment, 2022)
On 30th October 2020, an earthquake of magnitude 6.9 hit the Aegean coasts of Turkey and Greece. The epicentre was some 14 km northeast of Avlakia settlement on Samos Island, and 25 km southwest of Turkish town Seferihisar, Izmir. The destruction the earthquake caused concentrated mainly on the mid-rise RC buildings in certain districts of Izmir city. Among the diverse building typologies affected by the event are the traditional/vernacular hybrid timber-masonry and masonry buildings that are common to Turkey and Greece. This paper summarises and discusses the damage levels and mechanisms observed in these types of buildings, based on an extensive field and remote reconnaissance survey in the affected areas in both countries conducted by the Earthquake Engineering Field Investigation Team (EEFIT) of the UK Institute of Structural Engineers (IStructE). The observed damage is then discussed in light of the level of maintenance and occupancy status. The collected data are also used to empirically construct fragility curves, to assess whether a small sample can be used to describe the overall performance of the buildings in the area and how these compare to the outcomes of previous studies on comparable building stocks.